Highly efficient hydrodesulfurization driven by an in-situ reconstruction of ammonium/amine intercalated MoS2 catalysts - Tianlan Yan; Yingshuai Jia; Kaige Hou; Zhuxin Gui; Wenbiao Zhang; Ke Du; Di Pan; He Li; Yanghao Shi; Lu Qi; Qingsheng Gao; Yahong Zhang; et al. (iScience, 2024)
Summary: Hydrodesulfurization (HDS) is a commonly used route for producing clean fuels in modern refinery. Herein, ammonium/amine-intercalated MoS2 catalysts with various content of 1T phase and S vacancies have been successfully synthesized. Along with the increment of 1T phase and S vacancies of MoS2, the initial reaction rate of the HDS of dibenzothiophene (DBT) can be improved from 0.09 to 0.55 μmol·gcat−1·s−1, accounting for a remarkable activity compared to the-state-of-the-art catalysts. In a combinatory study via the activity evaluation and catalysts characterization, we found that the intercalation species of MoS2 played a key role in generating more 1T phase and S vacancies through the ‘intercalation-deintercalation’ processes, and the hydrogenation and desulfurization of HDS can be significantly promoted by 1T phase and S vacancies on MoS2, respectively. This study provides a practically meaningful guidance for developing more advanced HDS catalysts by the intercalated MoS2-derived materials with an in-depth understanding of structure-function relationships.